The Effects of Gross Domestic Product and Energy Consumption on Carbon Dioxide Emission in Uganda (1986-2018) - Otim, Jacob; Mutumba, Geoffrey; Watundu, Susan; Mubiinzi, Geoffrey; Kaddu, Milly (International Journal of Energy Economics and Policy, 2022)
This study examines the effects of energy consumption and per capita gross domestic product on carbon dioxide emission which is a precursor for global warming due to its large scale impact on the environment. The effect of per capita gross domestic product and per capita energy consumption on carbon emission per capita in Uganda is not clearly known. This study fill the empirical gap for Uganda for 1986-2018. The study used Vector Error Correction techniques and the results suggest evidence of a long-run relationship between the variables at a 5% significance level using the Johansen cointegration test. The estimated elasticity of carbon dioxide emission per capita with respect to gross domestic product per capita is 1.856.The results for the existence and direction of Granger causality show a unidirectional causality running from gross domestic product per capita to carbon dioxide emission per capita and the environmental Kuznets curve hypothesis is supported. In addition, there is no causal link between energy consumption per capita and gross domestic product per capita, which supports the growth neutrality hypothesis. The overall results indicate that gross domestic product per capita has a positive effect on carbon dioxide emission in Uganda while energy consumption does not Granger cause carbon dioxide emission.